Desenvolvimento e validação de arquétipos de radiologia para registro eletrônico de saúde - Araujo, Tiago Veloso [UNIFESP] (2016)
Purpose: To develop a sum of radiology archetypes for openEHR and to propose a method for the creation of new archetypes in many areas. Methods: There were been selected the modalities of radiology and imaging studies and the archetype entry classes. Using an archetype editor, they have been developed, based on specific terminologies for definition of terms and nouns, in English and Portuguese. The archetypes have been submitted to a validation tool, finishing their development. Results: There were been created 26 archetypes in thee 04 entry classes. In each one are inserted fields and general and specific information, according to the archetype class and type of study. Conclusion: The development of these archetypes creates a conceptual basis of radiology for an openEHR based Electronic Health Records (EHR), and enables the creation of archetypes based radiology systems. It also proposes a method for the development of new archetypes in other health areas.